2014
DOI: 10.9734/ajea/2014/6736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus and Bradyrhizobium japonicum on Growth and Chlorophyll Content of Cowpea (Vigna unguiculata (L) Walp)

Abstract: The field and screen house experiment was conducted at Tanzania Coffee Research Institute and Seliani Agricultural Research Institute respectively in Tanzania, between March-July 2013, to assess the effects of Bradyrhizobium japonicum and phosphorus on growth and total leaf chlorophyll content of cowpea. The experiment was out down in splitplot design whereby the main plots comprised two inoculation treatments (with and without B. japonicum), while the sub-plots contained phosphorus (TSP) application at four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
8
18
0
1
Order By: Relevance
“…Inoculated plants formed bigger nodules than uninoculated plants due to the effectiveness of the introduced rhizobia strain to initiate nodulation with cowpea roots which agrees with the report of Chiamaka (2014). A similar promoting effect of seed inoculation on dry weight of nodules per plant has also been reported by Bejandi et al (2011) and Nyoki and Ndakidemi (2014).…”
Section: Nodule Dry Weight/plantsupporting
confidence: 87%
“…Inoculated plants formed bigger nodules than uninoculated plants due to the effectiveness of the introduced rhizobia strain to initiate nodulation with cowpea roots which agrees with the report of Chiamaka (2014). A similar promoting effect of seed inoculation on dry weight of nodules per plant has also been reported by Bejandi et al (2011) and Nyoki and Ndakidemi (2014).…”
Section: Nodule Dry Weight/plantsupporting
confidence: 87%
“…This result agrees with the findings of [15] whom reported that Phosphorus fertilizer significantly enhanced growth and yield characters of the cowpea varieties used; plant height, leaf area, number of leaves and number of branches in all the weeks of measurement were significantly improved. This result is in conformity to the results observed earlier [16].…”
Section: Discussionsupporting
confidence: 93%
“…Gupta et al, (2005), they mentioned that plant height can also be increased significantly by inoculation of effective soybean rhizobial strains. These findings are confirming the observations of earlier workers Khan et al, (2014), Nyoki and Ndakidemi (2014). Seeds inoculated by different Rhizobium strains showed significantly higher nodulation, fresh root weight and root dry weight over control.…”
Section: Effect Of Inoculation On Plant Growthsupporting
confidence: 92%